Tilusrakenteen taloudelliset vaikutukset - Myyrä, Sami (MTT, 2002)
Suomalaiset tilat kärsivät pienestä peruslohkojen koosta. Suomessa kolme peruslohkoa neljästä on niin pieniä, että niiden koko aiheuttaa viljelyssä taloudellista haittaa. Näiden lohkojen osuus pinta-alasta on noin kolmannes. Toinen tärkeä tilusrakennetta kuvaava tekijä on peruslohkojen etäisyys talouskeskuksesta. Tässä tutkimuksessa ei saatu näyttöä siitä, että viljelyetäisyyksistä olisi taloudellista haittaa. Tilusrakenne ohjaa myös tuotantosuunnan valintaa, mikä puolestaan korostaa tilusrakenteen taloudellisia vaikutuksia. Tutkimuksessa tehdyt havainnot antavat viitteitä siitä, että peltojen pienestä koosta aiheutuvia haittoja on aliarvioitu. Jos epäedullisen tilusrakenteen haitat huomioitaisiin tilusjärjestelyiden kannattavuuslaskelmissa nyt lasketun suuruisina, nähtäisiin entistä useampi tilusjärjestelytoimenpide taloudellisesti kannattavana. Myös tilusjärjestelyjen suunnittelua tulisi tutkimustulosten mukaan muuttaa niin, että lohkokoon suurentamiselle annettaisiin aikaisempaa suurempi painoarvo. Suomen maataloudessa on käynnissä nopea rakennekehitys. Tilakoko kasvaa, mutta tilusrakenne ei parane. Tämän tutkimuksen tulokset osoittavat, että kyseinen kehitys vahvistaa tilusjärjestelyiden kysyntää.

Structural development is considered a primary requirement for the continuation of Finnish agricultural production and this need has been taken seriously by Finnish producers in recent years. Average farm size has grown very quickly. This growth has had a noticeable shattering effect on the dispersal of fields: those farms that remain in production receive from farms going out of production fields of poorer location/organization. Fields from farms that are going out of production have often not been added to neighbouring farms but rather due to land sales or rentals the distribution of acreage is sometimes very splintered and scattered. This study's purpose was to quantify the economic loss caused by having fields located at lesser or greater distances from one another. The first part of the study examines the influence of field and acreage distribution on field use. In the second part estimates of profitability are made using various production plans and profit calculations from part one. Field/acreage distribution shadow prices are deduced from the profit calculations. The study method used is representative of Heckman's two-part research method. The economic effects of various field/acreage distributions are simulated on the basis of estimated shadow prices. By using the profit calculations approach the study shows the costs and profits due to farm structure while still taking into account that field/acreage distribution influences a producer's decisions (such as the choice of production plans, crops, and production intensity). According to this study Finnish farms are harmed economically by small, scattered fields but current distances are not a statistically significant influence on overall farm profitability. Harm caused by having scattered acreage was shown to be dependant on farm size.
Keywords: ma; tilakoko; tilussuhteet; tilusjärjestely; structure of arable land; shadow price